Effects of Ocean Chlorophyll on the Mode Water Subduction Rate in the Northwestern and Central Pacific Ocean - Ma, Jinfeng; Yang, Qian; Liu, Hailong; Lin, Pengfei; Liu, Juan (Frontiers in Marine Science, 2022)
The effects of ocean chlorophyll on the mode water subduction rate in the subtropical mode water (STMW) and central mode water (CMW) in Pacific Ocean are investigated by performing two ocean-only experiments, using two different solar radiation penetration schemes, one with and one without chlorophyll effects. The biological impacts on mixed layer depth (MLD), upper ocean temperature and density are analyzed. Results show that the subduction rates of both STMW and CMW are increased with the effects of ocean chlorophyll. The increase in the subduction rate is mainly caused by the increased lateral induction term, which is related to larger MLD gradient in early spring in the chlorophyll experiment.